Problem międzynarodowej kontroli energii atomowej w polityce rządu Labour Party (1945–1951) - Rosiak, Artur (Acta Universitatis Lodziensis. Folia Historica, 2012)
After the Second World War, Clement Attlee’s government took an active part in developing an international system of the control of atomic energy. His plan for “full disclosure” became an important element of the signed November 15, 1945 Declaration of Washington, which allowed for the establishment of the UN Atomic Energy Commission. It was a compromised compilation of the British Prime Minister with the American plan of Vannevar Bush. The British Prime Minister was, therefore, co-creator of the UN Atomic Energy Commission. Based on the content of the Washington Declaration of 24 January 1946. The UN General Assembly unanimously adopted the draft resolution which created this Commission. During the first stage of the Atomic Energy Commission functioning, British diplomats took an active role. They realized that, given the rise of the “cold war”, the full potential of the original plan would not be reached. Therefore they actively supported the American plan of Baruch (Bernard Baruch Plan), which was similar to the British idea of creating an effective control system of atomic energy. It is difficult to assess the activities of the Labour Party politicians in the field of international disarmament during the key stages of 1947–1951. On one side, it should be noted that the priority objective outlined by Attlee in the “full disclosure” was not implemented. An international system of the control of atomic energy failed to be created. This was due to major differences in policy between government Powers and at first led to the impasse in the disarmament talks and then to a suspension of the meeting the Atomic Energy Commission in 1949. Since then, the problem of controlling and reducing nuclear armaments was transferred to the General Assembly, where in January 1952 they were able to establish a new body – the UN Commission on Disarmament.